Parenting and Motocross: The Whoops and Downs - Holst, Marissa E.; Stuhlsatz, Greta L. (Journal of Amateur Sport, 2017)
Parenting is a key contributor to socialization (Collins, Maccoby, Steinberg, Hetherington, & Bornstein, 2000). Many studies address the influences of parenting and contextual factors on child development (Belsky, 1984). Although long-term contextual factors have been shown to be associated with parenting behaviors (La Placa & Corlyon, 2016), little research exists on the degree to which short-term situational contexts may affect parenting. This study addressed two research questions 1) to identify both predictors and results of changes in parenting behaviors during the high investment sport of motocross bike racing and 2) to understand what effect the activity has on family dynamics. Survey data was collected from 33 parents at several child/adolescent competitions held at a Pronational Motocross track in Minnesota. A series of regression analyses were conducted followed by a path analysis. First, results indicated that levels of family cohesion, conflict, and achievement orientation affected parenting behavior before and after the race. Cohesion was positively related to increases in warmth expressed by the coaching parent, or the parent who spends the most time with the child trackside. Conflict was found to negatively predict expressed warmth by the coaching parent. Second, the results indicated that change in parenting behavior before and after a race was also associated with child behavior after the race.